2014
DOI: 10.5070/l26119613
|View full text |Cite
|
Sign up to set email alerts
|

Multi-storied Lives: Global Simulation as an Approach to Developing Multiliteracies in an Intermediate French Course

Abstract: Recent scholarship has proposed a pedagogy of multiliteracies to frame FL curricula and instruction, and encourage critical reflection about language use through a variety of discourses and textual genres. One pedagogical framework conducive to fostering learners' intersemiotic awareness is Global Simulation (GS). GS consists in the creation of a culturally grounded, fictitious scenario, wherein students adopt specific character roles through which they enact discourse styles associated with their characters' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 37 publications
(28 reference statements)
1
24
0
Order By: Relevance
“…Other studies on language teaching and learning have shown that simulations encourage the development and acquisition of language (e.g. Rising, 2009;Andreu-Andrés & García-Casas, 2011;Author, 2011;Woodhouse, 2011;Michelson & Dupuy, 2014;Blyth, 2018). The scholars coincide that simulations provide greater exposure to the target language, more purposeful interaction, more comprehensible input for learners, a reduced affective filter and lower anxiety in language learning.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on language teaching and learning have shown that simulations encourage the development and acquisition of language (e.g. Rising, 2009;Andreu-Andrés & García-Casas, 2011;Author, 2011;Woodhouse, 2011;Michelson & Dupuy, 2014;Blyth, 2018). The scholars coincide that simulations provide greater exposure to the target language, more purposeful interaction, more comprehensible input for learners, a reduced affective filter and lower anxiety in language learning.…”
Section: Related Workmentioning
confidence: 99%
“…It is the participants' responsibility to perform duties and thereby solve the problem without play-acting or inventing key facts (Jones, 2013). Michelson and Dupuy (2014) further discuss simulation and language learning and refer the simulation potential to enact discourse styles associated with social identities.…”
Section: Introductionmentioning
confidence: 99%
“…7 In contrast to the hierarchical Bloom's taxonomy, the knowledge processes (KP) framework offers a more robust and flexible tool for examining critical thinking, especially in the context of textual interaction. For this reason, the KP framework has been used to understand how students engage with authentic texts to interpret and transform meaning (Bhooth, Azman, & Ismail, 2015), to investigate instructor perceptions of multiliteracies pedagogy (Menke, 2018), to evaluate the present state of existing or revised curricula (Menke & Paesani, 2018;Rowland et al, 2014), and to analyze applications of multiliteracies and genre-based pedagogy (Michelson & Dupuy, 2014). For the purposes of this study, the KP framework serves to describe the instructional materials and highlight how the proposed training for peer responders aligns with the goals of the multiliteracies framework.…”
Section: Literacy-oriented Training For Peer Respondersmentioning
confidence: 99%
“…25-39). It does so by including an appropriate mix of knowledge processes-a curricular characteristic that has been deemed essential when implementing multiliteracies pedagogy (Kalantzis et al, 2016;Menke & Paesani, 2018;Michelson & Dupuy, 2014;Rowland et al, 2014). Second, as students move through the stages of the writing process (collaborative genre analysis, pre-writing, drafting, peer response, revision, and publication), they participate in "socially recognized ways of generating, communicating and negotiating meanings" and analyze "the relations between language users, texts, and contexts of use" (Warner & Michelson, 2018, pp.…”
mentioning
confidence: 99%
“…Thus, having students consider the voices not just of the writer, but those of the reader as well, can help L2 writers to make informed linguistic choices rooted in critical thinking about the subject matter. As with many simulation activities that deal with complex topics and cultural issues, teachers will want to make time in instruction to adequately prepare students beforehand and debrief with them afterward about the reading‐writing experience and their perceived learning (Michelson & Dupuy, ). Without those steps, there remains the danger that students rehearse and reify certain cultural stereotypes and assumptions, and/or misuse particular linguistic forms.…”
Section: Pedagogical Implications For Teaching the Personal Lettermentioning
confidence: 99%